PENENTUAN FORMASI BATUAN DENGAN PENGUJIAN LUMPUR SIRKULASI PEMBORAN - Sulardi Sulardi (PETROGAS: Journal of Energy and Technology, 2022)
This study aims to provide an overview of the drilling circulation mud testing method and the way of its interpretation in determining rock formations under the seabed. This research method uses a case study approach to the problem of the difficulty of determining the position of the end point bearing piling anchor flare stack offshore platform. From the results of the drilling mud circulation test, it can be seen that the types of felspafr and orthoclase rock formations at a depth of 1,785 feet below the seabed are considered suitable and suitable for anchor bearing end bearing piling offshore platforms. The results of this study also recommend that the mud circulation test method can be an alternative in determining rock formations for the installation of piling foundations for offshore platforms.